Nyctalus noctula subsp. noctula Schreber 1774 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Nyctalus noctula subsp. noctula Schreber 1774 Nyctalus noctula subsp. noctula Schreber 1774, Die Saugethiere, Vol. 1: 166. Type Locality: France. Synonyms: Nyctalus noctula subsp. altivolans White 1789; Nyctalus noctula subsp. lardarius Müller 1776; Nyctalus noctula subsp. magnus Berkenhout 1789; Nyctalus noctula subsp. major Leach 1818; Nyctalus noctula subsp. minima Fatio 1869; Nyctalus noctula subsp. palustris Crespon 1844; Nyctalus noctula subsp. princeps Ognev and Worobyev 1923; Nyctalus noctula subsp. proterus Kuhl 1818; Nyctalus noctula subsp. rufescens Brehm 1829. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 472, DOI: 10.5281/zenodo.7316519